Pengembangan Kurikulum Tingkat Satuan Pendidikan dalam Pembelajaran Karakter Bidang Studi IPS di SMP Negeri 1 Nglames Madiun - Iriani Takaria (Universitas Muhammadiyah Malang, 2013)
This research is a qualitative descriptive. The collection of data obtained by interview, observation and documentation was held in Pebruary, 2012 in SMPN 1 Nglames Madiun.The result showed that : 1) curriculum development programs in the areas of character study of learning in social studies IPS as a guide in providing socio-cultural, knowledge to the community was aware of character and dignity of life, the purpose of the program curriculum in social studies teaching character is to be able to organize educational activities in accordance with the characteristics of scholl. 2) form of curriculum development in field of learning the characters in the IPS study syllabus and lesson plane aremaking through the character through content standards and basic competence. 3) succesfull development of curriculum in the areas of character study of learning IPS yet there apperas anotable change in the students in their daily lives. 4) internal and external factors that support the succesful development of the curriculum in the areas character study of learning IPS is the principal must be able to carry out all activities according to their main objectives and content of external factor that support curriculum development KTSP in the field of study IPS is the involvement of school or departement of education public awareness of the environment.